HMGB1 down‐regulation mediates terameprocol vascular anti‐proliferative effect in experimental pulmonary hypertension. Issue 11 (9th March 2017) - Nogueira‐Ferreira, Rita; Ferreira‐Pinto, Manuel J.; Silva, Ana Filipa; Vitorino, Rui; Justino, Joana; Costa, Raquel; Moreira‐Gonçalves, Daniel; Quignard, Jean‐François; Ducret, Thomas; Savineau, Jean‐Pierre; Leite‐Moreira, Adelino F.; Ferreira, Rita; et al.
Abstract : Pulmonary arterial hypertension (PAH) is a progressive disease with a poor prognosis. Pulmonary artery smooth muscle cells (PASMCs) play a crucial role in PAH pathophysiology, displaying a hyperproliferative, and apoptotic‐resistant phenotype. In the present study, we evaluated the potential therapeutic role of terameprocol (TMP), an inhibitor of cellular proliferation and promoter of apoptosis, in a well‐established pre‐clinical model of PAH induced by monocrotaline (MCT) and studied the biological pathways modulated by TMP in PASMCs. Wistar rats injected with MCT or saline (SHAM group) were treated with TMP or vehicle. On day 21 after injection, we assessed bi‐ventricular hemodynamics and cardiac and pulmonary morphometry. The effects of TMP on PASMCs were studied in a primary culture isolated from SHAM and MCT‐treated rats, using an iTRAQ‐based proteomic approach to investigate the molecular pathways modulated by this drug. In vivo, TMP significantly reduced pulmonary and cardiac remodeling and improved cardiac function in PAH. In vitro, TMP inhibited proliferation and induced apoptosis of PASMCs. A total of 65 proteins were differentially expressed in PASMCs from MCT rats treated with TMP, some of which involved in the modulation of transforming growth factor beta pathway and DNA transcription. Anti‐proliferative effect of TMP seems to be explained, at least in part, by the down‐regulation of the transcription factor HMGB1. Our findings support the beneficial role of TMP in PAH and suggest that it may be an effective therapeutic option to be considered in the clinical management of PAH. Abstract : TMP‐reduced pulmonary and cardiac remodeling and hemodynamic features of PAH. Its vascular anti‐proliferative effect seems to be mediated by the protein HMGB1. TMP may be an effective therapeutic option in the clinical management of PAH.